The globalization of evidence-based policing: innovations in bridging the research-practice divide - Piza, Eric L.; Welsh, Brandon (Routledge, 2022)
"Evidence-based policing is based on the simple, but powerful, idea that crime prevention and crime control policy should be based on what works best in promoting public safety, as determined by the best available scientific evidence. Bringing together leading academics and practitioners, this book explores a wide range of case studies from around the world that best exemplify the integration of scientific evidence in contemporary policing processes. Chapters explore the transfer of scientific knowledge to the practice community, the role of officers in conducting police-led science, connection of work between police researchers and practitioners, and how evidence-based policing can be incorporated in daily police functions. The Globalization of Evidence-Based Policing is written for both researchers and practitioners interested in ensuring that scientific research is at centre stage in policing. Agencies (including law enforcement agencies, research centres, and institutions of higher learning) can look to these case studies as road maps to better foster an evidence-based approach to crime prevention and crime control. Those already committed to evidence-based policing can look to these chapters to ensure that evidence-based policing is firmly institutionalized within their agencies. An accessible and compelling read, this book is essential reading for all those interested in learning more about and doing more to bring about evidence-based policing"--